Dose-Escalated Hypofractionated Intensity-Modulated Radiotherapy in High-Risk Carcinoma of the Prostate: Outcome and Late Toxicity - David Thomson; Sophie Merrick; Ric Swindell; Joanna Coote; Kay Kelly; Julie Stratford; James Wylie; Richard Cowan; Tony Elliott; John Logue; Ananya Choudhury; Jacqueline Livsey (Prostate Cancer)
Background. The benefit of dose-escalated hypofractionated radiotherapy using intensity-modulated radiotherapy (IMRT) in prostate cancer is not established. We report 5-year outcome and long-term toxicity data within a phase II clinical trial. Materials and Methods. 60 men with predominantly high-risk prostate cancer were treated. All patients received neoadjuvant hormone therapy, completing up to 6 months in total. Thirty patients were treated with 57 Gy in 19 fractions and 30 patients with 60 Gy in 20 fractions. Acute and 2-year toxicities were reported and patients followed longitudinally to assess 5 year outcomes and long-term toxicity. Toxicity was measured using RTOG criteria and LENT/SOMA questionnaire. Results. Median followup was 84 months. Five-year overall survival (OS) was 83% and biochemical progression-free survival (bPFS) was 50% for 57 Gy. Five-year OS was 75% and bPFS 58% for 60 Gy. At 7 years, toxicity by RTOG criteria was acceptable with no grade 3 or above toxicity. Compared with baseline, there was no significant change in urinary symptoms at 2 or 7 years. Bowel symptoms were stable between 2 and 7 years. All patients continued to have significant sexual dysfunction. Conclusion. In high-risk prostate cancer, dose-escalated hypofractionated radiotherapy using IMRT results in encouraging outcomes and acceptable late toxicity.